2010
DOI: 10.1097/bpo.0b013e3181df1546
|View full text |Cite
|
Sign up to set email alerts
|

Escalators, Rubber Clogs, and Severe Foot Injuries in Children

Abstract: Level IV, Case Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 5 publications
0
17
0
4
Order By: Relevance
“…In 1 case series of 3 children whose hands became trapped in the side of an escalator, 2 suffered fractures of the third metacarpal, and all had damage to the extensor tendon of the middle finger . Fracture of the proximal phalanx of the first digit secondary to entrapment of the foot has also been described in a 2‐year‐old child . In this study, fractures were identified in 16.7% of patients, and all of these fractures were phalangeal.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In 1 case series of 3 children whose hands became trapped in the side of an escalator, 2 suffered fractures of the third metacarpal, and all had damage to the extensor tendon of the middle finger . Fracture of the proximal phalanx of the first digit secondary to entrapment of the foot has also been described in a 2‐year‐old child . In this study, fractures were identified in 16.7% of patients, and all of these fractures were phalangeal.…”
Section: Discussionmentioning
confidence: 59%
“…Some training groups require all of their dogs to wear protective footwear on the hind feet, as in their experience the hind paws are the most likely to become injured, b which is consistent with the findings in the present study. In people, certain types of shoes, in particular rubber clogs, have been implicated in the risk of entrapment while riding the escalator, and may potentially be associated with more severe injuries . There is currently no evidence for or against the use of protective footwear for dogs riding the escalator, and none of the dogs in this study were noted to be wearing footwear at the time of injury.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations